NON-RADIOLOGICAL IMPACT OF A NUCLEAR EMERGENCY: PREPAREDNESS AND RESPONSE WITH THE FOCUS ON HEALTH. Issue 1 (14th September 2018) - Carr, Z; Maeda, M; Oughton, D; Weiss, W
Abstract: Available experience from Chernobyl and Fukushima clearly demonstrate that nuclear emergencies may result in low and very low exposure levels, at which psychological and social effects among the affected population will dominate over the actual biological effects of ionising radiation. International protection standards and guidelines request, that both radiological and non-radiological health consequences have to be considered in preparedness and response to an actual emergency and there is a need to broaden the radiation protection system's philosophy beyond the metrics of radioactivity and radiation dose. During the past decade a number of multidisciplinary projects were set up with the aim of evaluating management options according to social, economic and ethical criteria, in addition to technical feasibility to achieve this goal. WHO and partners from the Inter-Agency Standing Committee Task Force on Mental Health and Psychosocial Support in Emergency Settings have developed a comprehensive framework and guidelines, which can be applied to any type of an emergency or disaster regardless of its origin. There is a need to include the available scientific expertise and the technical, managerial and personal resources to be considered within a similar 'decision framework' that will apply to radiation emergencies. Key areas of the required expertise needed to develop such a framework are radiation protection, medical support (especially primary care and emergency medicine, mental health support), social sciences (anthropology, psychology, ethics) and communications experts. The implementation of such a multidisciplinary concept in the operational world requires education and training well beyond the level currently available.